Problematika Pencegahan Perkawinan Anak di Desa Pamboborang - Dwi Utami Hudaya Nur; Mubakkirah, Fadhliah; An'nisah, Rizqi (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2023)
This research is qualitative research taking the research location in Pamboborang village, Banggae District, Majene Regency, West Sulawesi. A normative juridical and sociological research approach where the primary data sources for this research are parents and Pamboborang village officials. The results of this research state that promiscuity, pregnancy out of wedlock, culture and legal awareness are factors that greatly influence the high rate of child marriage in Pamboborang village. The role of law enforcers such as local government, the courts, the Regional Population and Family Planning Agency (BKKBD) and the Health Service are institutions that also have an important role in overcoming these factors. Socialization can be carried out well to educate and provide understanding about the positive and negative impacts of child marriage that occurs in Pamboborang village. It is hoped that the target of this education will be more focused on parents in Pamboborang village because parents should have the greatest role and responsibility to look after and protect their children from all negative actions and actions outside the home. Based on several factors that are the cause of the high rate of child marriage in Pamboborang village, it is hoped that the role of parents will be maximized, so that children who have fallen into promiscuity and juvenile delinquency will be taken in and educated better, rather than resorting to marriage. If the child is pregnant out of wedlock then the role of the parents is not only to get the child married, but the parents have a role to continue to provide advice and assistance to the child of the young couple, so that the marriage they build can create a happy and eternal marriage based on the Almighty God One.